Driving MSME Success: Unveiling the Impact of Digital Literacy, Financial Literacy, Innovation, and Human Capital - Petra, Dany Nofrizal; Innayah, Maulida Nurul; Purwidianti, Wida; Utami, Restu Frida (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
This study aimed to examine the effect of digital literacy, financial literacy, innovation, and human capital on MSME performance. This study used Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The population in this study consisted of MSMEs located in Banyumas Regency. Moreover, the sampling technique used in this study was convenience sampling, with the criteria that MSMEs were in Banyumas Regency and have been operating for at least 3 years, which resulted in 161 respondents. This study showed that digital literacy, innovation, and human capital have a positive and significant effect on MSME performance. In line with Resource-Based Theory (RBT), resources within organizations such as digital literacy, innovation, and human capital play an important role in facing competition to improve MSME performance. In addition, this study shows that financial literacy has not effect on MSME performance.